Increasing interest in social studies: Social perspective taking and self-efficacy in stimulating simulations - Gehlbach, Hunter; Brown, Scott W.; Boyer, Mark A.; Hudson, Natalie; Niv-Solomon, Anat; Maneggia, Donalyn; Janik, Laura L.; Ioannou, Andri (My University, 2008)
This study examined the potential of simulations to bolster interest in middle school social studies classrooms. Using a pre–post-design, we examined 305 middle school students (49% female) who participated in the web-based GlobalEd simulation. In contrast to the motivation declines middle school students usually experience, participants in this simulation became more interested in social studies. We investigated four hypotheses as to why these increases may have occurred. We found no support for the possibility that, (a) students’ interest in a particular issue area or (b) their increased valuing of the subject matter, were related to their increased interest. However, results suggested that, (c) the challenging nature of the activity and (d) students’ increased propensity to engage in social perspective taking may have bolstered their interest in social studies. The discussion explores future research directions and whether implications for classroom teachers are warranted given the correlational nature of the research.
Keywords: Social studies classrooms; Social perspective taking; Self-efficacy; Social studies